Structure activity relationship of pyrazinoic acid analogs as potential antimycobacterial agents - Hegde, Pooja V. (2023)
Tuberculosis (TB) remains a leading cause of infectious disease-related mortality and morbidity. Pyrazinamide (PZA) is a critical component of the first-line TB treatment regimen because of its sterilizing activity against non-replicating Mycobacterium tuberculosis (Mtb), but its mechanism of action has remained enigmatic. PZA is a prodrug converted by pyrazinamidase encoded by pncA within Mtb to the active moiety, pyrazinoic acid (POA) and PZA resistance is caused by loss-of-function mutations to pyrazinamidase. We have recently shown that POA induces targeted protein degradation of the enzyme PanD, a crucial component of the coenzyme A biosynthetic pathway essential in Mtb. Based on the newly identified mechanism of action of POA, along with the crystal structure of PanD bound to POA, we designed several POA analogs using structure for interpretation to improve potency and overcome PZA resistance. We prepared and tested ring and carboxylic acid bioisosteres as well as 3, 5, 6 substitutions on the ring to study the structure activity relationships of the POA scaffold. All the analogs were evaluated for their whole cell antimycobacterial activity, and a few representative molecules were evaluated for their binding affinity, towards PanD, through isothermal titration calorimetry. We report that analogs with ring and carboxylic acid bioisosteres did not significantly enhance the antimicrobial activity, whereas the alkylamino-group substitutions at the 3 and 5 position of POA were found to be up to 5 to 10-fold more potent than POA. Further development and mechanistic analysis of these analogs may lead to a next generation POA analog for treating TB.